Bilirubin and bile acids in osteocytes and bone tissue. Potential role in the cholestatic‐induced osteoporosis. (13th October 2020) - Ruiz‐Gaspà, Silvia; Guañabens, Núria; Jurado, Susana; Combalia, Andreu; Peris, Pilar; Monegal, Ana; Parés, Albert
Abstract: Background and Aims: Osteoporosis is a common complication in patients with primary biliary cholangitis. Both bilirubin and lithocholic acid (LCA) result in detrimental effects on osteoblastic cells, and ursodeoxycholic acid (UDCA) counteracts these outcomes. However, there is no information on the consequences of these retained substances of cholestasis and sera from cholestatic patients in osteocytes. Methods: The impact of bilirubin, LCA, UDCA and serum from jaundiced patients on viability, differentiation, mineralization and apoptosis has been assessed in MLO‐Y4 and MLO‐A5 osteocyte cell lines. Effects on gene expression were assessed in these cells and in human bone fragments. Results: Lithocholic acid 10 μmol/L and bilirubin 50 μmol/L decreased viability in MLO‐Y4 and MLO‐A5 cells (11% and 53% respectively; P ≤ .01). UDCA alone or combined with LCA or bilirubin increased cell viability. Jaundiced sera decreased cell viability (56%), an effect which was reverted by UDCA. Bilirubin decreased differentiation by 47% in MLO‐Y4 ( P ≤ .01) and mineralization (87%) after 21 days in MLO‐A5 ( P ≤ .03). Both bilirubin and LCA increased apoptosis in MLO‐Y4, and UDCA diminished the apoptotic effect. Moreover, bilirubin down‐regulated RUNX2 and up‐regulated RANKL gene expression in bone tissue, MLO‐Y4 and MLO‐A5 cells, and LCA up‐regulated RANKL expression in bone tissue. UDCA 100 μmol/L increased the gene expression of all these genes in bone tissue and MLO‐Y4 cells and neutralized the decreased RUNX2 expression induced by bilirubin. Conclusion: Bilirubin and LCA have damaging consequences in osteocytes by decreasing viability, differentiation and mineralization, increasing apoptosis and modifying gene expression, effects that are neutralized by UDCA.